1992
DOI: 10.1002/bit.260390611
|View full text |Cite
|
Sign up to set email alerts
|

Acetic acid formation in escherichia coli fermentation

Abstract: Acetic acid formation in Escherichia coli fermentation has been studied in continuous cultures. Experimental results suggest that the limited capacity of the oxidative metabolism (perhaps the limited capacity of TCA cycle) may be responsible for acetic acid formation. At low growth rates, both anabolic and catabolic requirements may be satisfied by the oxidative metabolism. However, at high growth rates these two demands may exceed the capacity of the oxidative metabolism alone. It is proposed that under these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
115
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(122 citation statements)
references
References 15 publications
7
115
0
Order By: Relevance
“…Acetate production and secretion is an overflow mechanism generally interpreted as resulting from an imbalance between carbon uptake/availability and the metabolic network capacity to use it for energy and biomass production 24 . On the other hand, it is also an important source of energy generation through substrate-level phosphorylation 25 . In addition to acetate secretion, we found that both GLPK and DKI strains also secrete significant levels of D-lactate (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Acetate production and secretion is an overflow mechanism generally interpreted as resulting from an imbalance between carbon uptake/availability and the metabolic network capacity to use it for energy and biomass production 24 . On the other hand, it is also an important source of energy generation through substrate-level phosphorylation 25 . In addition to acetate secretion, we found that both GLPK and DKI strains also secrete significant levels of D-lactate (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All attribute acetate formation either to limitations in respiratory NADH turnover and concomitant ATP generation through oxidative phosphorylation (Andersen & von Meyenburg, 1980;Doelle et al, 1982;Reiling et al, 1985;Varma & Palsson, 1994) or to initial limitations in the TCA cycle (Majewski & Domach, 1990;Han et al, 1992). Moreover, Han et al (1992) concluded that these limitations cause a reorganization of the catabolic flux distribution to meet the anabolic demands at high growth rates by generating the necessary amount of energy by using both oxidative metabolism and acetic acid formation.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that during rapid aerobic growth, E. coli produces acetate as a by-product. The metabolism of E. coli switches from respiration to fermentation when cells grow at a high specific growth rate with a low glucose concentration even under aerobic conditions (3,10). It has been suggested that an increase in cell growth rate presumably increases glucose uptake rate and intracellular glucose concentration (23).…”
Section: Discussionmentioning
confidence: 99%